The exposition of practice as research as experimental systems (Palíndromo, 2019)
Michael SchwabEditor of the Journal for Artistic Research (JAR)Translation Osmar Yang and Yara GuasqueArticle originally published in English (SCHWAB, Michael. "The Exposition of Practice as Research as Experimental Systems", 2014, pp. 31-40) as a chapter in the book CRISPIN, Darla; GILMORE, Bob (Eds.). Artistic Experimentation in Music. An Anthology. Leuven: Leuven University Press, 2014.